Design and Analysis of Commercially Viable Free-Space Optical Communication Link for Diverse Beam Divergence Profiles - Singh, Harjeevan; Miglani, Rajan; Mittal, Nitin; Gaba, Gurjot Singh; Masud, Mehedi; Aljahdali, Sultan (Frontiers in Physics, 2021)
With an exponential increase in the use of smart devices and with increasing demand for high-speed data applications, the Radio Frequency and Microwave links will find themselves almost incapable of meeting this deficit. Free-space optical (FSO) links are poised to take the leading role as communication systems for futuristic needs in providing cost-effective and high-speed connectivity to end-users. However, on the flip side, the reliability of FSO links has an intrinsic relationship with the characteristics of the atmospheric channel. During the propagation, the atmospheric adversities result in the geometrical spreading of the FSO beam which in turn has consequential degrading effects on the link performance. In this work, an FSO communication system based on practical, commercial, and realistic parameters has been proposed with the intent of accurately determining the co-relation between different beam divergence profiles and overall link performance. For different beam divergence profiles, the proposed link has been evaluated for reference bit error rate (BER) of 10-9 which is an ideal condition for delivering high-speed data access to the end-users. During the analysis, the practical constraints related to the trade-off between the maximum possible link range and beam divergence have also been optimized. The findings of this work will be crucial for engineers and designers in configuring FSO links enhanced link range and reliability.